Establishment of perennial forages intercropped with soybean for integrated crop-livestock systems - Machado, Luís Armando Zago; Cecato, Ulysses; Comunello, Eder; Concenço, Germani; Ceccon, Gessi (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate soybean (Glycine max) grain yield and the establishment of perennial intercropped forages. Soybean was evaluated in sole crop and intercropped with the following forages: Megathyrsus maximus, Aruana and BRS Tamani cultivars; Urochloa brizantha, Xaraés, BRS Piatã, and BRS Paiaguás cultivars; U. decumbens; and U. ruziziensis. A randomized complete block design was used, with seven replicates, in the 2011/2012 and 2012/2013 crop seasons. In the intercropped system, the forages were sown 21 and 14 days after soybean emergence, in the first and second crop seasons, respectively. Grain yield did not differ for soybean in sole crop or intercropped, except for soybean + U. ruziziensis and soybean + 'BRS Paiaguás', which were less productive in the second year of evaluation. The 'BRS Tamani' forage was the most suited for intercropping with soybean, considering its morphological characteristics and its low competition potential. Soybean intercropped with perennial forages contributes to suppress weed growth and, overall, does not compromise soybean yield.